Lesões bucomaxilofaciais: estudo dos casos periciados de 2007 a 2013 no Instituto Médico Legal Nina Rodrigues - Salvador / BA - Dias, Isabella de Andrade [UNESP] (2015)
The maxillofacial trauma is one of the issues most important public health in the world, influenced by factors of social, cultural and economic. The functional and anatomical changes caused by physical damage can affect the individual psychologically, by the loss or impairment of chewing ability, speech and aesthetics. The peculiarities of the lesions, this study aimed to describe the epidemiological profile, assessing victims as well as the types, causes and resulting from maxillofacial trauma caused by violence and accidents, and injuries caused by dental work. The methodological design of the study was analytical-descriptive, cross-sectional, and were evaluated retrospectively from January 2007 to December 2013, 3,600 periciados of reports with head and neck injuries treated in the Dental Clinic of the Institute of Forensic Medicine Nina Rodrigues, Salvador BA. We evaluated 3,455 reports relating to assaults, traffic accidents and accidents in general, relating to socio-demographic profile, affected region, damage, and resulting etiologic agent. The data in this block were analyzed by chi-square test or the chi-square test of the likelihood ratio, defined using the V Cramer coefficient to quantify the association. It was found that there was a higher prevalence of cases involving 56.06% male, 80.72% and 72.19% adults faiodermas; of abuse has significant number of occurrences (74.18%), reaching the hard and soft tissues (42.72%). It was identified as well, the predominance of dento-alveolar lesions compared to the total number of maxillofacial trauma (67.73%); caused by blunt agent (92.72%)...